Modeling of hard disk drives for shock and vibration analysis – consideration of nonlinearities and discontinuities - Yap, Fook Fah; Harmoko, Hendri; Liu, Mengjun; Vahdati, Nader (Nonlinear dynamics, 2007)
This paper reviews recent advances (mostly after year 2000) in shock and vibration analysis of hard disk drives (HDD) considering the presence of nonlinearities and discontinuities. Components and dynamic phenomena in HDD where effects of mechanical nonlinearity and discontinuities are significant are discussed, e.g., head actuator suspension, dimple and slider, head–disk interface, fluid dynamic bearing, spinning disks, and load/unload dynamics. Ways to model these nonlinearities and discontinuities are reviewed in detail. Our research on modeling an entire HDD in operating mode subject to shock and vibration using a flexible multibody dynamics formulation is also presented. The numerical simulation of the shock response of a 1-in. form factor HDD is presented. A half-sinusoidal acceleration shock is applied at the base of the HDD. Response of the flying height for different shock amplitudes and duration times is simulated.